Using middle finger length to determine the internal diameter of uncuffed tracheal tubes in paediatrics1. (26th July 2018) - Ritchie‐McLean, S.; Ferrier, V.; Clevenger, B.; Thomas, M.
Summary: The selection of an appropriately‐sized tracheal tube is of critical importance in paediatric patients to reduce both the risk of subglottic stenosis from a tracheal tube that is too large, and inadequate ventilation or poor end‐tidal gas monitoring from a tracheal tube that is too small. Age formulae are widely used, but known to be unreliable, often resulting in a need to change the tracheal tube. Previous work has shown that the length of the middle finger and the internal diameter can both be used to guide depth of tracheal tube insertion. Therefore, we hypothesised that middle finger length may also be related to tube internal diameter. We enrolled children aged up to 12 years presenting to our institution for elective anaesthesia and measured the length of the middle finger on the palmar aspect of the hand. Anaesthetists chose the airway device they felt most appropriate for the procedure, and were unaware of the middle finger measurement. Of 160 patients who were enrolled, 108 were included in the final analysis. We found a linear relationship between uncuffed tracheal tube internal diameter and median middle finger length for each size of tracheal tube. Relationship between middle finger length and cuffed tracheal tube internal diameter was less clear. We propose that the formula: 'middle finger length (cm) (round up to nearest 0.5) = internal diameter of uncuffed tracheal tube (mm)' may be an improvement compared with age formulae for selecting uncuffed tracheal tubes in children, although this requires formal testing.